A RELATIONSHIP BETWEEN ARTERIAL STIFFNESS, CYTOKINE LEVELS, AND BONE MINERAL DENSITY IN WOMEN WITH POSTMENOPAUSAL OSTEOPOROSIS - S. Yu. Tsarenok; V. V. Gorbunov; T. A. Aksenova (Научно-практическая ревматология, 2018)
Arterial stiffness is an independent predictor of cardiovascular diseases. A possible link between the development of osteoporosis (OP) and cardiovascular diseases is presently being considered. Cytokines that can affect the skeletal and cardiovascular systems act as pathogenetic factors of this interaction. Objective: to identify a relationship between the measures of arterial stiffness, the serum level of cytokines and the state of bone mineral density (BMD) in women with OP; to establish the role of elevated cytokine concentrations in lowering BMD and raising pulse wave velocity (PWV) in this category of patients. Subjects and methods. A total of 115 postmenopausal women were examined. X-ray densitometry was used to investigate BMD in two areas: the lumbar vertebrae and the proximal femur. Carotid-femoral PWV was measured by applanation tonometry. The serum level of cytokines was investigated by enzyme immunoassay. Results and discussion. Women with osteoporosis were found to have a higher PWV and elevated concentrations of interleukin (IL) 6, IL-8, tumor necrosis factor-α, IL-4, and IL-10. The higher level of IL-6 is an independent factor in decreasing proximal femur bone BMD and in increasing PWV.